Clinical characteristics and identification of risk factors of testicular torsion in children: A retrospective study in a single institution - Zhang, Kaiping; Zhang, Yin; Chao, Min (Frontiers in Surgery, 2023)
Background: Testicular torsion (TT) is a common urological emergency posing serious health problem in children. Prompt diagnosis and treatment of TT are very important for children to protect the affected testis. The aim of this study was to evaluate the historical features, physical examination findings, laboratory tests, and ultrasound examinations in children with TT, as well as to identify the predictors of testicular salvage in children. Materials and Methods: We conducted a retrospective record of clinical findings, laboratory data, ultrasound findings, operating results, and the results of follow-up in hospitalized children with TT from January 2017 to December 2021. A multivariable logistic regression model was used to identify predictors of testicular salvage. Results: A total 102 hospitalized children who presented with TT were included. Of these patients, patients were aged from 1 month to 16 years, with a median age of 7.71 years. TT is significantly more common in the winter. Of these patients, 77 torsions were left-sided, 24 were on the right side and only 1 was bilateral sides. Meanwhile, we detected that 88 children suffering from TT were intravaginal torsion of the spermatic cord, and the rest of children were outside. Anticlockwise torsion was found in 65 cases (63.73%), clockwise torsion in 37 (36.27%). As a result, 60 underwent orchidectomy, while 42 had a scrotal exploration with fixation of the testis. Multivariate analysis showed that cause of TT, time to intervention, white blood cell (WBC) and mean platelet volume (MPV) were correlated with the risk of a surgical outcome. Conclusions: Only a small proportion of TT children received timely surgical management. Testicular salvage can be predicted by cause of TT, time to intervention, WBC and MPV. Early scrotal exploration based on careful physical examination decreases the risk of misdiagnosis of spermatic cord torsion. A certain percentage of children with TT presenting with scrotal trauma or epididymo-orchitis should have their testicles checked to make sure that they do not have torsion, especially those visitors in cold season.